Bronchial adenoma masquerading as pneumonia: a rare case report - Kumar, Nitin; Kumar, Naresh; Sharma, Prakhar; Lohchab, Komal (Indian Journal of Case Reports, 2017)
A 29-year old non-smoker woman presented with breathlessness, cough with minimal expectoration and hemoptysis. Serial chest X-rays were suggestive of progressive collapse of right lung field. CECT chest revealed large endobronchial lesion in right main bronchus and obstructive collapse consolidation of right lower lobe and part of the middle lobe. Fiberoptic bronchoscopy revealed an endobronchial mass obstructing the right main bronchus. This reddish polypoid mass bleed on touch that was suggestive of bronchial adenoma and it was confirmed by histopathological examination. Patient was treated empirically with anti-tubercular drugs due to high prevalence of tuberculosis in our setting; however, the patient had clinical deterioration. Following the histopathology report, the diagnosis of bronchial adenoma was established. Bronchial adenoma should be considered in a young female patient presenting with hemoptysis and obstructive pneumonia.